New distributed model for predicting erosion-type pollution by integrating sediment connectivity and watershed model. (April 2023) - Zhu, Kaihang; Chen, Lei; Li, Leifang; Wang, Yiwen; Yan, Xiaoman; Chen, Jieying; Feng, Chenghong; Shen, Zhenyao
Abstract: A distributed model was proposed by coupling the index of sediment connectivity (IC) and the SWAT model (IC-SWAT). Sediment delivery ratio (SDR) was used to quantify the sediment deposition and the SWAT model was used to obtain the spatiotemporal distribution of soil P. The proposed model was then applied to a mountainous watershed in Three Georges Reservoir Region, China. The results suggested that the IC-SWAT model had better performance on simulation of SY and PP, while the traditional SWAT model overestimated the area of hotspots of SY and PP by 6.7% and 5.2%. Returning cropland to forest and fertilizer reduction on the cropland with the highest soil P could remove 3.51% and 1.05% of PP, indicating cropland with the highest soil P should be preferentially controlled. The proposed model offers an approach for soil erosion and erosion-type NPS pollution simulation, and provides strategies for management practices on grid-scale. Highlights: A new model (IC-SWAT) was proposed for erosion-based pollution prediction. Distributed sediment delivery and temporal soil pollution were incorporated. The IC-SWAT provides more accurate predictions than existing models. Hotspots and key periods were identified for erosion-based pollution. Suggestions were given for erosion-based pollution using the IC-SWAT.